Legal Position of Land Sale and Purchase Agreement with Fully Certified Land Under Hand Against the Interests of the Heirs - Wahyuni, Ayuni Sri; Sri Darmadi, Nanang (Jurnal Konstatering, 2024)
This research aims to analyze: 1) The legal position of private sale and purchase agreements. 2) Legal protection for heirs who use a sale and purchase agreement in full under their hands. This type of research falls within the scope of normative legal research. The approach methods used in this research are the case study approach and the statutory approach. This type of data uses secondary data obtained from literature studies. The data analysis method used in this research is prescriptive. The research results were concluded: 1). The legal position of a signed sale and purchase agreement in full is that it has the power of proof in a case and its truth cannot be denied, so the private letter must be legalized. The Civil Code regulates private deeds as described in Articles 1874, 1874a, and Article 1880. These articles require that every private deed must be accompanied by a dated statement, given by a notary or other official recognized by Constitution.  2) Legal protection for heirs who use a private sale and purchase agreement in full has several forms, although in this context, legal protection may be more limited compared to using an authentic sale and purchase agreement made before a Notary/PPAT. However, some forms of protection that can be obtained are Proof of Writing, Acknowledgment of Signature: If the signature of the seller's heir is recognized as authentic and valid, this can provide proof that the agreement was indeed signed by the party concerned, Witness Attestation, and Transaction Integrity. However, it should be remembered that a private sale and purchase agreement does not usually have the same legal force as an official deed registered with an authorized government agency.